SAT0382 Arthrosonographic Findings in Crystal Arthropathies. (23rd January 2014) - Bergner, R.; Peters, L.; Schmitt, V.; Sattler, H.; Löffler, C.
Abstract : Background: At the time, crystal arthropathies (CA) (e.g. calcium pyrophosphate crystal deposition disease (CPPD) and gout (GA)) can be diagnosed definitely only by microscopic investigation of joint effusion with polarisation filter, especially if the clinical aspect is atypical. Objectives: It is known that gout arthritis (GA) can show a typical double contour (DC) sign in joint ultrasound. Previous studies investigated only GA compared with non crystal arthropathies (NCA). But there are no data about the sensitivity and specificity of different sonographic findings in NCA, compared with GA and CPPD. We investigated the sensitivity and specificity of sonographic findings in GA and CA (GA + CPPD) in patients with GA, CPPD and NCA. Methods: In this observational study we analyzed arthrosonographic findings like synovitis (SYN), hypervascularisation (HV) and a DC sign in patients who underwent diagnostic joint puncture. Relevant were only the findings in the punctured joint. SYN and HV were measured semiquantitatively on a scale from 0 – 3. The joint effusion was investigated with native microscopy and with polarisation filter. Sensitivity and specificity were calculated for the different findings for GA alone and crystal arthritis (GA and CPPD) in general. Results: Analyzed were 103 patients with 113 punctered joints. In 39 joints we found GA, in 17 CPPD and in 57 NCA, respectively. Investigated were knee joints (n=74), small finger or toe joints (n=10), elbows (n=5), ankle (n=12), shoulders (n=6) and wrists (n=6). SYN was 2.2±0.8 (GA), 2.4±0.8 (CPPD) and 2.3±0.8 (NCA) (n.s.), respectively. HV was 2.2±1.0 (GA), 1.9±1.0 (CPPD) and 1.2±1.1 (NCA); (p<0.001 GA vs. NCA and p=0.03 CPPD vs. NCA), respectively. DC was found in 36 of 39 patients with GA, in 14 of 17 patients with CPPD and 7 from 57 with NCA, respectively. The sensitivity and specificity of DC was 92% and 72% for GA, and 89% and 88% for CA in general. For HV ≥ 2 sensitivity and specificity was 69% und 51% for GA and 71% and 60% fpr CA in general. If HV ≥ 2 and positive DC were combined specificity increased to 80% for GA and 93% for CA, but sensitivity decreased to 67% and 66%, respectively. There was no significant difference in serum uric acid between GA and CPPD (9.8±3.4 and 7.6±4.2 mg/dl) at the time of joint puncture. Conclusions: Ultrasonography has good sensitivity and specificity to diagnose CA in general. If a DC was detected and the HV was ≥ 2, more than 90% of CA were detected, but arthrosonography was weak in differentiation of GA and CPPD. A joint puncture is still necessary to differentiate GA and CPPD. Disclosure of Interest: None Declared